1979
DOI: 10.2307/1936967
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Primary Productivty of Lamto Savannas, Ivory Coast

Abstract: Lam~o savan~as (Ivory Coast) are characterized by the heterogeneity of their structure and by their dynamic evolutt.o~ towards forest. Life-forms and phenological cycles of herbs, shrubs, and trees reflect .the cons~rammg factors ?f the environment. Biomass and productivity are largely dependent on soil and chmate. The specific cycles of above-and belowground biomass allow an estimat~ of the primary productivity. Production of shrubs and trees, obtained from size-biomass correlatiOns and growth measures, is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
145
3
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 11 publications
15
145
3
3
Order By: Relevance
“…This is in agreement with previous research conducted under controlled environmental conditions (Wynn and Bird, 2007). Moreover, studies conducted in West African savannas as well as pantropical productivity estimates both show that more than half of the net primary productivity of these ecosystems is attributable to C 4 grasses (Lloyd et al, 2008;Menaut and Cesar, 1979). This agrees well with the notion that, at least in non-coarse textured soils, SOC sequestration potential per unit productivity must be inherently lower for C 4 dominated locations, which is further confirmed by the comparatively lower SOC G. Saiz et al: Influence of C 3 /C 4 on SOM in tropical biomes 5053 concentrations observed at grass-dominated locations (Saiz et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with previous research conducted under controlled environmental conditions (Wynn and Bird, 2007). Moreover, studies conducted in West African savannas as well as pantropical productivity estimates both show that more than half of the net primary productivity of these ecosystems is attributable to C 4 grasses (Lloyd et al, 2008;Menaut and Cesar, 1979). This agrees well with the notion that, at least in non-coarse textured soils, SOC sequestration potential per unit productivity must be inherently lower for C 4 dominated locations, which is further confirmed by the comparatively lower SOC G. Saiz et al: Influence of C 3 /C 4 on SOM in tropical biomes 5053 concentrations observed at grass-dominated locations (Saiz et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Forty-five percent of species belonging to this group started flowering while leafing at the end of the dry season or at the beginning of the www.intechopen.com rainy season, while 30% completed reproduction entirely during the dry season (figure 3). The contribution of this group to flora were higher in Sudanian and Guinean bioclimatesincluding in the mosaic landscape of savannas and forests in the Lamto region (Menaut, 1971;Menaut & César, 1979) -than in drier bioclimates (figure 5). One species with reverse phenology was observed in this group: Faidherbia (Acacia) albida.…”
Section: Phenological Strategies: Characteristics and Distributionmentioning
confidence: 93%
“…Therefore, fire objectively defines a recruitment stage, where a tree acquires a perennial, fire-resistant trunk instead of producing resprouts each year from belowground organs, like a grass tuft. Based on average flame height, Menaut and César [52] considered Seedlings are identified by the presence of cotyledons or their small size together with the absence of record at their location at the previous census. Resprouts have a perennial belowground system and an annual aboveground systems, i.e., all stems or their tallest stem bear no fire scars.…”
Section: Fire and The Definition Of Demographic Stagesmentioning
confidence: 99%